Keterbukaan Perdagangan, Inflasi, Jumlah Tenaga Kerja dan Pertumbuhan Ekonomi di Indonesia - Ifa , Khoirul; Tri Indrianasari, Neny; Setyo Liyundira, Fetri (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2020)
This research is a quantitative study using time series data from 1986 to 2018, research data obtained from the world bank, data analysis techniques using the GMM method to see the impact of trade openness on economic growth. The test results using the Generalized Method of Moments analysis method show that all variables have a significant effect on the dynamics of economic growth in Indonesia.. Then this value also has a probability of less than the ? value. It can be concluded that the variables of trade, inflation, and the number of workers have a significant effect on economic growth in Indonesia.